Novel platinum(IV) complexes conjugated with a wogonin derivative as multi-targeted anticancer agents. Issue 8 (15th April 2017) - Qin, Xiaodong; Xu, Gang; Chen, Feihong; Fang, Lei; Gou, Shaohua
Graphical abstract: Highlights: A series of multi-targeted platinum(IV) complexes conjugated with wogonin, a natural product, via a linker group were designed and synthesized to study their anticancer effects. Compound10, the conjugate containing wogonin and cisplatin units, displayed the best anticancer activity, comparable to cisplatin, by inhibiting COX and inducing the accumulation of ROS in addition to damaging DNA. Abstract: Platinum-based complexes like cisplatin and oxaliplatin are well known the mainstay of chemotherapy regimens on clinic. Wogonin, a natural product that possesses wide biological activities, is now in phase I clinical test as an anticancer agent in China. Herein reported are a series of novel Pt(IV) complexes that conjugated a wogonin derivative (compound3 ) to the axial position via a linker group. After being tethered to the platinum(IV) complexes, the wogonin derivative provided multiple anticancer effects, especially in compound10, a fusion containing wogonin and cisplatin units. Compound10 not only inherited the genotoxicity from cisplatin, but also obtained the COX inhibitory property from the wogonin derivative. Further mechanistic investigation revealed that compound10 caused the accumulation of ROS, decreased the mitochondrial membrane potential ( ΔΨm ) and then activated the p53 pathway. Overall, the research demonstrates that the "integrative" prodrug can be an effective strategy to promote the anticancer potency of Pt-based drugs for cancer treatment.